2009
DOI: 10.1167/iovs.09-3451
|View full text |Cite
|
Sign up to set email alerts
|

A NewFgf10Mutation in the Mouse Leads to Atrophy of the Harderian Gland and Slit-Eye Phenotype in Heterozygotes: A Novel Model for Dry-Eye Disease?

Abstract: The mutation in the Fgf10 gene leads to a dominant slit-eye phenotype caused by atrophy of the Harderian gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Furthermore, defect in FGF10 leads to the development and differentiation of several ocular tissues. [26][27][28] In our previous study of microRNA-328, retinoic acid, and TGF-b were shown to be involved in the same network regulation leading to the development of myopia.29 A recent study indicated that retinoic acid could regulate the TGFb pathway in the control of FGF10 expression.30 Therefore, the present study focuses on the involvement of FGF10 in the development of myopia.The present study aims to discover the role of FGF10 in myopia by the following methods: (1) measuring the FGF10 expression during the development of myopia in mice, (2) testing for the association between single nucleotide polymorphisms (SNPs) of FGF10 and high myopia in a Chinese cohort residing in Taiwan, and (3) evaluating the possible biologic consequence of the associated SNP. …”
mentioning
confidence: 99%
“…Furthermore, defect in FGF10 leads to the development and differentiation of several ocular tissues. [26][27][28] In our previous study of microRNA-328, retinoic acid, and TGF-b were shown to be involved in the same network regulation leading to the development of myopia.29 A recent study indicated that retinoic acid could regulate the TGFb pathway in the control of FGF10 expression.30 Therefore, the present study focuses on the involvement of FGF10 in the development of myopia.The present study aims to discover the role of FGF10 in myopia by the following methods: (1) measuring the FGF10 expression during the development of myopia in mice, (2) testing for the association between single nucleotide polymorphisms (SNPs) of FGF10 and high myopia in a Chinese cohort residing in Taiwan, and (3) evaluating the possible biologic consequence of the associated SNP. …”
mentioning
confidence: 99%
“…32 Such traits as eyeball volume recovered by the proposed method can also help researchers and clinicians better understand eye growth patterns under certain disease conditions, [47][48][49][50] the mechanisms vision systems follow to maintain visual clarity, 51,52 and key genes affecting visual pathways. [53][54][55][56][57][58] Although the proposed method enables estimation of a 3D eyeball structure from the corresponding 2D flatmount image, it can be further improved in the following ways in the future. (1) The dissection process might be improved by etching or partially eroding the sclera to relax the tissue to reduce wrinkling or bulging.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports about eyelid function and eye accessory organs in adult EOB mice, because many studies have been focused on eyelid development at various embryonic stages. A previous study reported that shrinkage of the harderian gland in Fgf10 mutant mice could lead to corneal disease, due to defects in eyeball wetting (Puk et al, 2009). In conclusion, studies on eyelid function in EOB models would promote early diagnosis, prevention, and therapy for human heredity congenital eye disease, and development of relevant drugs.…”
Section: Gene Namementioning
confidence: 99%